Phosphorylation of the Archaeal Holliday Junction Resolvase Hjc Inhibits Its Catalytic Activity and Facilitates DNA Repair in Sulfolobus islandicus REY15A - Huang, Qihong; Mayaka, Joseph Badys; Zhong, Qing; Zhang, Chao; Hou, Guihua; Ni, Jinfeng; Shen, Yulong (Frontiers in Microbiology, 2019)
Protein phosphorylation is one of the main protein post-translational modifications and regulates DNA repair in eukaryotes. Archaeal genomes encode eukaryotic-like DNA repair proteins and protein kinases (ePKs), and several proteins involved in homologous recombination repair (HRR) including Hjc, a conserved Holliday junction (HJ) resolvase in Archaea, undergo phosphorylation, indicating that phosphorylation plays important roles in HRR. Herein, we performed phosphorylation analysis of Hjc by various ePKs from Sulfolobus islandicus. It was shown that SiRe_0171, SiRe_2030, and SiRe_2056, were able to phosphorylate Hjc in vitro. These ePKs phosphorylated Hjc at different Ser/Thr residues: SiRe_0171 on S34, SiRe_2030 on both S9 and T138, and SiRe_2056 on T138. The HJ cleavage activity of the phosphorylation-mimic mutants was analyzed and the results showed that the cleavage activity of S34E was completely lost and that of S9E had greatly reduced. S. islandicus strain expressing S34E in replacement of the wild type Hjc was resistant to higher doses of DNA damaging agents. Furthermore, SiRe_0171 deletion mutant exhibited higher sensitivity to DNA damaging agents, suggesting that Hjc phosphorylation by SiRe_0171 enhanced the DNA repair capability. Our results revealed that HJ resolvase is regulated by protein phosphorylation, reminiscent of the regulation of eukaryotic HJ resolvases GEN1 and Yen1.